The relationship between anatomy and electrical parameters in His bundle pacing. (14th October 2021) - Coluccia, G; Senes, J; Corallo, S; Aste, M; Oddone, D; Donateo, P; Puggioni, E; Brignole, M
Abstract: Background: The relationship between anatomy and electrical parameters of His bundle (HB) pacing has not been extensively studied. Purpose: To characterize the anatomical location of the HB lead tip and its relationship with acute electrical parameters. Methods: Consecutive patients who underwent HB lead implantation, guided by standard fluoroscopy and electrophysiology, were prospectively enrolled. The relationship between HB lead tip and tricuspid valve plane (TVP) was assessed with post-procedure transthoracic echocardiography. Results: Twenty-five patients were studied. In 11 patients (44%), the HB lead tip did not cross the TVP (A group): in 7 cases it was screwed in the right atrium at a mean distance of −6.1 mm from the TVP and, in 4 cases, at the level of the tricuspid annulus. In the remaining 14 patients (56%), the lead tip crossed the TVP (V group): it was screwed in the right ventricle at a mean distance of 9.3 mm from the TVP. A and V groups had comparable HB capture thresholds (1.6±1 V vs 1.7±0.7 V, 1 ms pulse-width; p=0.66); selective HB capture was significantly more represented in the A group (91% vs 21%; p=0.001). Significantly higher R-wave amplitudes were seen in the V group (6.7±3 vs 2.5±1.7 mV; p=0.0004), and they positively correlated with the distance from the TVP (p=0.0038). Atrial oversensing was never observed. Conclusion: In a consecutive cohort of HBP recipients, the rate of patients who had an effective HB capture in the atrium was substantial and was characterized by different electrophysiological properties than in the ventricle. Funding Acknowledgement: Type of funding sources: None.